Enhancing Students' Writing Skills: The Impact, Engagement, and Optimization of Automated and Teacher Written Corrective Feedback - Lestari, Endah; Tusino, Tusino; Rokhayati, Titi (Universitas Pendidikan Ganesha, 2025)
This study examined the effectiveness of combining Automated Writing Corrective Feedback (AWCF) and Teacher Written Corrective Feedback (TWCF) in improving students’ writing skills at SMK Bina Karya 2 Karanganyar. A mixed-methods approach was employed using an explanatory sequential design. Quantitative data from pre- and post-writing tests showed a significant improvement in mechanics, grammar, vocabulary, organization, and content of descriptive texts (t(58) = 8.888, p < .001). Qualitative findings from interviews and questionnaires indicated that students engaged with feedback in behavioral, cognitive, and affective dimensions. Low-proficiency students accepted most automated corrections, while advanced learners selectively applied feedback. AWCF was most effective for surface-level errors, while TWCF provided deeper support in content, coherence, and organization. A structured feedback process, where students revised based on automated corrections before receiving teacher guidance, ensured iterative improvement and minimized cognitive overload. The combination of AWCF and TWCF fostered self-regulated learning, reduced writing anxiety, and enhanced overall proficiency. Student perceptions varied; 78% found AWCF helpful for grammar, but only 42% believed it improved overall writing. Teachers noted that TWCF provided clearer explanations, reinforcing deeper learning. The integration of AWCF and TWCF enabled students to develop both linguistic accuracy and higher-order writing skills. These findings underscore the importance of a hybrid feedback model balancing efficiency, personalization, and engagement, ultimately enhancing students' writing proficiency in a structured and effective manner.